Modeling the Response of the Langtang Glacier and the Hintereisferner to a Changing Climate Since the Little Ice Age - Wijngaard, René R.; Steiner, Jakob F.; Kraaijenbrink, Philip D. A.; Klug, Christoph; Adhikari, Surendra; Banerjee, Argha; Pellicciotti, Francesca; van Beek, Ludovicus P. H.; Bierkens, Marc F. P.; Lutz, Arthur F.; Immerzeel, Walter W. (Frontiers in Earth Science, 2019)
This study aims at developing and applying a spatially-distributed coupled glacier mass balance and ice-flow model to attribute the response of glaciers to natural and anthropogenic climate change. We focus on two glaciers with contrasting surface characteristics: a debris-covered glacier (Langtang Glacier in Nepal) and a clean-ice glacier (Hintereisferner in Austria). The model is applied from the end of the Little Ice Age (1850) to the present-day (2016) and is forced with four bias-corrected General Circulation Models (GCMs) from the historical experiment of the CMIP5 archive. The selected GCMs represent region-specific warm-dry, warm-wet, cold-dry, and cold-wet climate conditions. To isolate the effects of anthropogenic climate change on glacier mass balance and flow runs from these GCMs with and without further anthropogenic forcing after 1970 until 2016 are selected. The outcomes indicate that both glaciers experience the largest reduction in area and volume under warm climate conditions, whereas area and volume reductions are smaller under cold climate conditions. Simultaneously with changes in glacier area and volume, surface velocities generally decrease over time. Without further anthropogenic forcing the results reveal a 3% (9%) smaller decline in glacier area (volume) for the debris-covered glacier and a 18% (39%) smaller decline in glacier area (volume) for the clean-ice glacier. The difference in the magnitude between the two glaciers can mainly be attributed to differences in the response time of the glaciers, where the clean-ice glacier shows a much faster response to climate change. We conclude that the response of the two glaciers can mainly be attributed to anthropogenic climate change and that the impact is larger on the clean-ice glacier. The outcomes show that the model performs well under different climate conditions and that the developed approach can be used for regional-scale glacio-hydrological modeling.